The evaluation of braking efficiency of tractor transport aggregate - Janulevičius, Algirdas; Giedra, Kazimieras (Transport, 2002)
The theoretical investigation of the braking process of a tractor transport aggregate is carried out. The influence of the mass of machines on the efficiency ofbraking is set. The dependencies of forces acting the coupler on the trailer and tractor ratio of masses ( λ c ), and on the difference of ratios of the brekable and whole masses of a trailer and tractor (λp – λt), are presented. The nomogram for operative set and the selection of the main braking parameters of various tractor transports aggregates were established. With the help of the nomogram it is possible to set: braking efficiency, greatest deceleration, shortest braking distance, greatest common mass of aggregate and acting forces of brakable tractor transport aggregate.First Published Online: 19 Dec 2011